2015
DOI: 10.1002/rcm.7215
|View full text |Cite
|
Sign up to set email alerts
|

Methods of lipid‐normalization for multi‐tissue stable isotope analyses in tropical tuna

Abstract: Models using published estimates for parameters from other species cannot be used. Based on a range of lipid content that do not exceed 45%, we recommend the linear model to correct the bulk δ(13)C values in the investigated tissues but the parameters have to be estimated from a proportion of the original data for which chemical extraction is required and the isotopic values of bulk and lipid-free tissues are measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 81 publications
(149 reference statements)
4
15
0
Order By: Relevance
“…The C and N contents of juvenile rainbow trout differed according to the tissue considered (F = 62.8 and 29.1, respectively, p < 0.001, Figure ; Tables S2 and S3, supporting information), a result consistent with literature data regarding the rainbow trout O. mykiss . The C content in muscle, liver, red blood cells and plasma ranged between 40% and 50% and from 30% to 40% in external tegument (including mucus and scales) and pectoral fin.…”
Section: Resultssupporting
confidence: 87%
“…The C and N contents of juvenile rainbow trout differed according to the tissue considered (F = 62.8 and 29.1, respectively, p < 0.001, Figure ; Tables S2 and S3, supporting information), a result consistent with literature data regarding the rainbow trout O. mykiss . The C content in muscle, liver, red blood cells and plasma ranged between 40% and 50% and from 30% to 40% in external tegument (including mucus and scales) and pectoral fin.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the absence of significant fluctuations in lipid concentrations in this tissue over the reproductive cycle suggests that white muscle only plays a minor role in the supply of energy for gonad maturation. As a highly migratory species, the muscle metabolism enables for burst swimming (Korsmeyer & Dewar, 2001;Sardenne et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…1D Elliott et al, 2014), and may also explain discrepancies among the different equations present in the literature Yurkowski et al, 2015). Sardenne et al (2015) found little correlation between δ 13 C values in tuna muscle lipid-extracted using dichloromethane and δ 13 C estimated using arithmetic correction factors derived from experiments using chloroform-methanol, and concluded that "published estimates from other species cannot be used". The difference may be partially due to variation in solvent rather than species-specific differences.…”
Section: Discussionmentioning
confidence: 91%